L’assurance construction éléments de terminologie - Béguin, Louis-Paul (Assurances)

(untitled) (HEC Montréal, 1982)
Builder's Risk insurance is very elaborate and rather complicated. It has a technical vocabulary of its own which Mr. Béguin has studied in this article. We have pleasure in submitting it to our readers even if it is considered by the author to be a preliminary survey. A.